Exposure to prevention information, sexual health, and experience of discrimination: HIV exploration among high-risk populations in Vietnam - Tram N.T. Huyen; Somying Pumtong; Sermsiri Sangroongruangsri; Luerat Anuratpanich (GarVal Editorial Ltda., 2023)
Context: HIV/AIDS has been a major public health concern worldwide, yet research on high-risk populations in Vietnam has paid little attention to prevention information, sexual behaviors, and discrimination. Aims: To investigate the above-mentioned groups' exposure to prevention information, sexual health, and experiences of discrimination. Methods: The cross-sectional paper-based survey focusing on HIV-related risk behaviors, testing, and access to health services was administered to participants recruited through two-stage sampling in southern Vietnam. The questionnaire consisted of four sections, including sociodemographic characteristics, sexual behaviors, access to preventive information, and discrimination experience. Results: Among the 173 participants, approximately 60% identified as lesbian/gay/bisexual/transgender, with 51.4% reporting they had a potential risk of HIV acquisition and 85% engaging in high-risk sexual behaviors. Television was the most popular source of information on HIV prevention. The most common unsafe behavior among respondents was non-condom use during sex (72% in males and 25% in females), followed by drug use (41% in males and 7.4% in females). Significant disparities were identified in STI diagnosis, treatment, and HIV testing rates among sociodemographic groups (such as orientation, education, occupation, monthly income, and financial vulnerability). Discrimination experiences were also associated with different sociodemographic characteristics (such as men who have sex with men orientation, occupation, and engagement in high-risk sexual behaviors). Conclusions: Policymakers can allocate financial resources and support evidence-based interventions to address the HIV epidemic among high-risk populations in Vietnam, including educational campaigns on television, healthcare provider training programs, and stigma reduction efforts.